The practical reality of learning assessment in initial teacher training from the perspective of students vs teachers - Gallardo-Fuentes, Francisco; Carter-Thuillier, Bastian; Peña-Troncoso, Sebastian; Añazco-Martínez, Luis; Gallardo-Fuentes, Jorge (Institute of Advanced Engineering and Science, 2025)
A central issue in the initial training of physical education teachers lies in the dominance of traditional assessment systems that fail to fully support student learning and engagement. This study addresses this issue by identifying the assessment systems used in four university campuses in the southernmost region of Chile, comparing the perspectives of teachers and students. A sample of 538 students (M=21.8, SD=2.9) and 60 teachers (M=42.9, SD=12.3) was surveyed using the “Questionnaire for the study of the assessment system in the initial training of physical education teachers”. The results revealed significant differences between students and teachers in their perception of the importance of cognitive abilities and the coherence of syllabus elements. Traditional assessment tools were used more frequently, and students attributed failed assessments to issues with teaching methods. Additionally, students perceived having less influence on grading processes. These findings suggest a need for reform in assessment practices, emphasizing more formative and participatory approaches to better align with student needs and improve the learning process in physical education teacher training. The practical applications of the study facilitate implementing formative assessment in physical education with active feedback and training teachers in shared assessment.